2018
DOI: 10.1071/mf17096
|View full text |Cite
|
Sign up to set email alerts
|

Response of demersal fish assemblages to an extreme flood event in a freshwater-deprived estuary in South Africa

Abstract: The Kariega Estuary in South Africa, is an example of a freshwater-deprived estuary. Large-scale water abstraction and droughts have resulted in this estuary either being uniformly marine or hypersaline. A major episodic flood event in October 2012, the largest ever recorded in this system, provided us with an opportunity to investigate the prolonged effect of an episodic flood on the demersal fish assemblage of a freshwater-deprived estuary. A beam trawl net was used for sampling the fish assemblages from Dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…The salinity gradients of both the Kariega and Bushmans estuaries have been severely compromised for decades (Hodgson, 1987; Ter Morshuizen & Whitfield, 1994; Strydom, Whitfield & Paterson, 2002; Vorwerk et al, 2008). Large floods, such as those in the Kariega Estuary in 2011 and 2012, have been shown to result in the reestablishment of a salinity gradient for up to 2 years (Nodo et al, 2018). However, the estuaries persistently return to a marine‐dominated state, as recorded in this study, owing to severe freshwater deprivation.…”
Section: Discussionmentioning
confidence: 99%
“…The salinity gradients of both the Kariega and Bushmans estuaries have been severely compromised for decades (Hodgson, 1987; Ter Morshuizen & Whitfield, 1994; Strydom, Whitfield & Paterson, 2002; Vorwerk et al, 2008). Large floods, such as those in the Kariega Estuary in 2011 and 2012, have been shown to result in the reestablishment of a salinity gradient for up to 2 years (Nodo et al, 2018). However, the estuaries persistently return to a marine‐dominated state, as recorded in this study, owing to severe freshwater deprivation.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the concentration of early juveniles in the upper reaches of turbid, freshwater-rich estuaries, such as the Great Fish, and the absence of early juveniles in the clear, freshwater-deprived Kariega Estuary, Whitfield and Paterson (2003) suggested that freshwater abstraction reduces the nursery habitat available to A. japonicus in this region. Confirming the importance of freshwater input and increased turbidity to the recruitment of A. japonicus, Nodo et al (2018) also found that settlement stage A. japonicus (30 -100 mm TL) were only recorded in the freshwater deprived Kariega Estuary following major river flooding and increases in turbidity and food resources in the middle and upper reaches of the estuary.…”
Section: Discussionmentioning
confidence: 57%
“…The dusky kob, Argyrosomus japonicus, is a widely distributed sciaenid, which occurs in temperate and subtropical waters of the Indian and Pacific Oceans around Africa, Australia, India, Pakistan, China, Korea, and Japan (Silberschneider and Gray, 2008). Spawning occurs in the nearshore marine environment in the vicinity of estuaries, reefs and the surf-zone (Silberschneider and Gray, 2008), with settlement stages in South Africa (10 -30 mm TL) (Griffiths, 1996;Pattrick and Strydom, 2014;Nodo et al, 2018) and eastern Australia (from ~4 weeks post-hatching) (Russell et al, 2021a) recruiting into estuaries soon after spawning. Argyrosomus japonicus in South Africa is most likely estuarine-dependent, with the early juveniles (< 150 mm TL) thought to occur exclusively in estuaries and the larger juveniles found in estuaries and nearshore coastal waters (Griffiths, 1996;Cowley et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a study conducted in the same estuary by Nodo et al . () found that after episodic river flooding, G. aestuaria was absent from beam‐trawl catches. Once flood waters have dissipated however and zooplankton stocks recovered, G. aestuaria abundance shows a positive response to flooding events (Martin et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Following the recovery of estuarine food resources after a river flood ( e.g . increasing zooplankton abundance) however, the fish stocks usually respond positively (Forbes & Cyrus, ; Vorwerk et al, ), with river pulses entering the sea promoting the recruitment of marine fish species into adjacent estuaries (James et al, ; Vorwerk et al, ; Nodo et al, ).…”
Section: Introductionmentioning
confidence: 99%